Workplace Dynamics and Employee Commitment at CV Kevin Perkasa: Dinamika Tempat Kerja dan Komitmen Karyawan di CV Kevin Perkasa - Gustamin , Kevin Oktaviano; Abadiyah , Rifdah (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Employee commitment has become a crucial determinant of organizational sustainability in today’s competitive business environment. Specific Background: Companies often face challenges related to job insecurity, work stress, and job satisfaction, which directly influence employees’ dedication and performance. Knowledge Gap: However, empirical evidence in small-scale property marketing firms, particularly in Indonesia, remains limited. Aims: This study aims to examine how job insecurity, job stress, and job satisfaction contribute to employee commitment at CV Kevin Perkasa. Results: Using quantitative methods and multiple linear regression with 50 respondents, findings reveal that job insecurity, job stress, and job satisfaction each have a positive and significant relationship with employee commitment, both partially and simultaneously. Novelty: Unlike previous studies focusing on large organizations, this research highlights how psychological and motivational factors jointly strengthen commitment in small property enterprises. Implications: The results suggest that improving job security perceptions, managing stress effectively, and fostering satisfaction can enhance workforce stability and organizational resilience. Highlights: Job insecurity, stress, and satisfaction significantly shape employee commitment. Study emphasizes psychological aspects in small property firms. Findings provide strategic insights for human resource sustainability. Keywords: Job Insecurity, Job Stress, Job Satisfaction, Employee Commitment, Human Resource Management